Analisis Perbandingan Kekuatan Struktural Poros Roda Kereta Api Menggunakan Metode Finite Element Analysis - Putra Firmansyah, Ganda; Abdi, Ferly Isnomo; Ganda, Andita Nataria Fitri; Davareza, Tinton; Mubarok, Dio Dwi (Jurnal Rekayasa Mesin, 2026)
This study presents a comparative analysis of the structural strength of two railway axle models using the Finite element analysis (FEA) method. The objective is to determine the effect of geometric variations on stress distribution, total deformation, and safety factor of the railway axle. Three-dimensional models of both axle designs were developed using CAD software and analyzed through the Static Structural module in ANSYS Workbench 17.2. The material used is ASTM A36 carbon steel with a static load of 196,133 N, representing the axle load of a railway system. Simulation results show that Model A exhibits better structural performance, with a maximum Von Mises stress of 136.72 MPa, maximum deformation of 0.10697 mm, and a minimum safety factor of 1.6164. In contrast, Model B produces a higher maximum stress of 163.64 MPa and a total deformation of 0.15741 mm, with a lower minimum safety factor of 1.3505. These differences indicate that geometry significantly affects the load distribution and structural stability of the axle. Overall, Model A is considered more optimal due to its higher stiffness and greater safety margin, making it more suitable for railway axle design applications that require high vertical load resistance and low fatigue risk.